The Influence of the Inquiry Learning Model on Science Learning Outcomes of SDN 23 Ampenan Students - Maya Aprianty; Darmianty Darmianty; Baiq Niswatul Khair (International Journal of Social Service and Research, 2023)
This study aims to determine whether there is influence of the inquiry learning model on student learning outcomes in science learning. This inquiry learning model has the main advantages of five important components, namely asking questions, formulating hypotheses, collecting data, analyzing data, and making conclusions that can improve student learning outcomes. This research is a semi-experimental study with a non-equivalent control group design. The sample in this study consisted of two classes, namely the experimental class and the control class. The data collection instrument uses a description test that meets validity and reliability. The results of this study indicate that there are differences in student learning outcomes between the experimental class using the inquiry learning model and the control class using the conventional learning model. Because the average value of the experimental class is higher, it is concluded that there is an influence of the inquiry learning model on student learning outcomes.